Depressive symptoms and attitudes towards smoking in young people - Yazıcı, Hikmet; Çetinkaya, Bünyamin; Kahveci, Harun; Demirci, Serpil (Journal of Dependence, 2007)
Objective: The aim of this study was to investigate relationship between depressive symptoms and smoking attitudes in young people. Method: The sample was composed of 406 young smokers people (279 male and 127 female). The Beck Depression Inventory (BDI) was administered in order to evaluate the depressive symptoms. For the evaluation of smoking attitudes Smoking Attitudes Inventory (SAI) was used. Check list was administered in order to evaluate age, gender, incomes, smoking period and smoking amount. For smoking amount, smoking period and depressive symptoms, comparisons between groups were made using independent t test. Pearson correlation coefficients were used to assess the rellationship between depressive symptoms and smoking attitudes. Results: On avarage, participants have smoked 14.97 cigarettes a day and smoked throughout 7.54 years. Females reported significantly lower levels of daily smoking amounts (M = 13.18, SD = 7.29) than males (M = 16.76, SD = 8.10), t (406) = -4.42, p< .001. Females also reported significantly lower levels of smoking periods (M = 5.78, SD = 5.13) than males (M = 9.30, SD = 7.76), t (406) = -5.43, p< .001. Depressive symptoms was positively correlated with cognitive attitudes (r= .28, p< .001), control (r= .28, p< .001), action (r= .30, p< .001) and self-direction (r= .43, p< .001). Conclusion: Findings suggests that there is a relation between some smoking attitudes and depressive symptoms. Smoking attitudes may play a central role in smoking behaviour. Findings suggests also that depresed people more likely to smok.